Sharia green crowdfunding as a sustainable financing solution for halal MSMEs empowerment - Jasmine, Jannatul; Rohim, Ade Nur (LPMP Imperium, 2024)
This research investigates Sharia green crowdfunding as a sustainable mechanism for halal Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. It addresses the gap between environmentally conscious financing and Islamic finance principles, demonstrating how this integration supports the objectives of a green economy. Through a systematic literature review, the study identifies the challenges faced by halal MSMEs. It evaluates the effectiveness of Sharia-compliant financing in improving access to capital. The findings indicate that Sharia-based crowdfunding platforms are crucial for advancing sustainable finance and are aligned with environmental, social, and governance (ESG) principles. The proposed Sharia Green Crowdfunding model provides a new framework for acquiring capital, promoting responsible business practices, and enhancing collaboration between Islamic Financial Institutions and halal MSMEs. Ultimately, this contributes to national economic development. In conclusion, Sharia Green Crowdfunding is vital for Indonesia's ambition to become a global hub for a sustainable Islamic economy. Public interest statements This research enhances the discussion on sustainable development while following Islamic financial principles. It can act as a model for other emerging economies aiming to blend religious and environmental factors into their financial systems.